2001
DOI: 10.1897/1551-5028(2001)020<1216:eotsee>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF THE SYNTHETIC ESTROGEN 17α-Ethinylestradiol ON THE LIFE-CYCLE OF THE FATHEAD MINNOW (PIMEPHALES PROMELAS)

Abstract: A fish full life-cycle (FFLC) study was conducted for 17 alpha-ethinylestradiol (EE2) using the fathead minnow, Pimephales promelas. Newly fertilized embryos (< 24 h old) were exposed to five concentrations of EE2 (0.2, 1.0, 4.0, 16, and 64 ng/L nominal) in continuous flow-through conditions for 305 d at 25 +/- 1 degrees C. Exposure concentrations were verified by 14C-EE2 radiochemistry, supported by radioimmunoassay, and mean measured values were > or = 70% of nominal. For the F0 adult phase until 301 d posth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
211
1
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 208 publications
(230 citation statements)
references
References 32 publications
14
211
1
4
Order By: Relevance
“…However, the number of investigated species is low and test endpoints might not always be sensitive. A variety of authors have reported endocrine-disruptive effects on different animals in ng L -1 concentration ranges [9,10,11]. Unfortunately, no toxicity data for copepods, which seem to be most sensitive in this study, are available.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, the number of investigated species is low and test endpoints might not always be sensitive. A variety of authors have reported endocrine-disruptive effects on different animals in ng L -1 concentration ranges [9,10,11]. Unfortunately, no toxicity data for copepods, which seem to be most sensitive in this study, are available.…”
Section: Discussionmentioning
confidence: 93%
“…In fish first toxic effects were reported between 1 and 100 ng L -1 [8,9,10]. For invertebrates, Vandenberg et al showed effects on the sexual development of the amphipod Hyalella azteca in the concentration range 100 to 3420 ng L -1 [11].…”
Section: Introductionmentioning
confidence: 99%
“…EE2 induzierte Vitellogenin in juvenilen Karpfen bei 10 ng/L und in männlichen Regenbogenforellen bereits bei einer Konzentration von 0.1 ng/L [1,6]. In einer Langzeitstudie mit dem Fisch Pimephales promelas wurden Entwicklungsstö-rungen bei Konzentrationen von 4 ng/L beobachtet [7]. Diese Befunde deuten darauf hin, dass EE2 schon in sehr niedrigen Konzentrationen in Fischen Wirkungen hervorruft, die durch eine Störung des endokrinen Systems ausgelöst werden.…”
Section: Introductionunclassified
“…Diese Konzentrationen sind deutlich niedriger als populationsrelevante Effektkonzentrationen für die primären Zielorganismen Fische. Länge et al[7] berichten eine "No-observable-effect"-Konzentration (NOEC) für EE2 von 1 ng/L für die Spezies Pimephales promelas in einer 2-Generationen-Studie, bei der Entwicklung, Wachstum, Reproduktionserfolg sowie histopathologische Veränderungen an den Gonaden und Vitellogeninsynthese untersucht worden waren. Scholz und Gutzeit[30] ermittelten eine NOEC für EE2 von 1 ng/L für Oryzias latipes bezüglich Reproduktion und gonadosomatischem Index, nachdem die Fische über 2 Monate nach Eiablage exponiert worden waren.…”
unclassified
“…Synthetic estrogens such as ethinyl estradiol can feminize fish, reduce fertilization rates, and obliterate populations at concentrations from 1 to 6 ηg/L (Länge et al 2001, Parrott and Blunt 2005, Kidd et al 2007. Synthetic steroids used for growth promotion in cattle can masculinize fish (Ankley et al 2001(Ankley et al , 2003.…”
Section: Endocrine Effectsmentioning
confidence: 99%